ACSL4 promotes the formation of the proliferative subtype in hepatoblastoma - Wei Dang; Qin Li; Xiaoying Wang (BMC Cancer)
Abstract Hepatoblastoma (HB) is the most common pediatric liver malignancy, with its significant heterogeneity complicating the identification of the most aggressive subtypes and the development of targeted therapies. In this study, we performed transcriptomic analysis of HB samples from the GEO database and identified three distinct molecular subtypes with varying prognostic outcomes. Among them, the proliferative subtype, characterized by enhanced proliferative capacity, poor prognosis, and an immunosuppressive tumor microenvironment, was particularly notable. ACSL4 emerged as a critical biomarker of this proliferative subtype, driving HB cell proliferation both in vitro and in vivo. Furthermore, pharmacological inhibition of ACSL4 using abemaciclib significantly suppressed tumor growth in xenograft models. Mechanistically, ACSL4 was found to promote cell proliferation by downregulating the interferon response signaling pathway which may implicate contribution to immunosuppression in the tumor. These findings underscore the pivotal role of ACSL4 in HB progression and highlight its potential as a therapeutic target for aggressive HB subtypes.